Kepemimpinan yang Berhasil Melalui Pemahaman Tipe dan Fungsi - Nur Asyifa Ananda; Ahmadi Ahmadi (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Leadership in education plays a crucial role in influencing the performance and motivation of organizational members. This study examines various types and functions of leadership, including transformational leadership, which significantly enhances teacher performance and creates an innovative learning environment. Through a literature review, it is found that adaptive leaders who understand the socio-cultural context can effectively manage change, thus creating an atmosphere conducive to learning. Additionally, this study highlights the importance of leadership development strategies that focus on interpersonal skills and active participation of members in the decision-making process. The findings indicate that a deep understanding of leadership types and their application in the educational context can enhance the overall quality of education, as well as encourage higher engagement from all stakeholders in achieving desired educational goals.